2018
DOI: 10.1021/acs.estlett.8b00200
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Online Monitoring for Assessing Removal of Bacteria by Reverse Osmosis

Abstract: Rigorous monitoring of microbial water quality is essential to ensure the safety of recycled water after advanced treatment for indirect and direct potable reuse. This study evaluated real-time bacterial monitoring for assessing reverse osmosis (RO) treatment for removal of bacteria. A strategy was employed to monitor bacterial counts online and in real time in the RO feed and permeate water using a realtime continuous bacteriological counter. Over the course of 68 h pilot-scale testing, bacterial counts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
3
15
1
3
Order By: Relevance
“…Further details of the real-time instrument can be found elsewhere. 16 Conductivity of RO feed and permeate was analyzed using Orion Star™ A322 Conductivity meters (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Analytical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further details of the real-time instrument can be found elsewhere. 16 Conductivity of RO feed and permeate was analyzed using Orion Star™ A322 Conductivity meters (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…11,14 This is because of the protocol for ensuring pathogen removal using rather conservative surrogate performance indicators: removal of total organic carbon (TOC) and/or electrical conductivity (EC). 9,15 Fujioka et al, 16 have recently demonstrated the potential of continuously measuring bacterial removal by RO through real-time counting of bacterial number in RO feed and permeate. Although the direct counting method was expected to help ensuring bacterial removal considerably greater than conventional methods, their study identified bacterial removal of lower than 3-log (99.9%).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the frequency of backwashing at the full-scale plant during this 132 study period was once every three days, however, throughout the year it can vary depending on the increase in turbidity or the head loss of the filters. To reduce the background interference from dissolved organics (humic acid-like organic matter) that are not counted but can mask autofluorescence of bacteria, an online sample dilution method that was previously reported in literature (Fujioka et al, 2018) was applied. Before analysis, the filter influent and effluent underwent 50-and 3-fold dilution using the pure water, respectively (Fig.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…Another online bacterial counting technique that has recently emerged is a real-time bacteriological counting technology, which is also based on simultaneous light-scattering and autofluorescence measurements (Pepper and Snyder, 2016;Fujioka et al, 2018). This technology utilizes the combined autofluorescence emitted from riboflavin and nicotinamide adenine dinucleotide -hydrogen (NADH) in bacterial cells to identify them in water.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there is a need for real-time feedback on counts of viable bacteria in purified water systems to facilitate informed, timely decision making. Newly available online instrumentation is proposed to fulfill this need of real-time bioburden detection [6, 9, 17], with the added potential to detect viable, but nonculturable bacteria that would otherwise be missed by culture-based methods [21]. Online water bioburden analyzers (OWBAs) commonly probe the HPW with a 405 nm laser, which yields detection of bacteria through the combination of bacterial scattered light and endogenous autofluorescence, which is excited by the violet light (observation of scattered light only would suggest non-biological particulate matter) [6].…”
Section: Introductionmentioning
confidence: 99%